Microstructure evolution and hot corrosion behavior of Zr-Y modified silicide coating prepared by two-step process. (1st August 2019) - He, Jiahua; Guo, Xiping; Qiao, Yanqiang
Graphical abstract: Highlights: Zr-Y modified silicide coatings were successfully prepared by a two-step process. The microstructural evolution of the two-step coating was detailed investigated. The coating could protect the substrate from hot corrosion at 900 °C for 100 h. The released Cl2, sulfur from molten salts could accelerate oxidation of the coating. Abstract: Zr-Y modified silicide coating on the Nb-Si based ultrahigh temperature alloy is prepared by firstly magnetron sputtering Ti-5Al-10Nb-2Zr (at.%) alloy film and then Si-Y co-deposition. The coating is mainly composed of a TiSi2 outer layer, a relatively thick (Nb, X)Si2 inner layer and a thin transitional layer. The mass gain of the bare alloy, simple Si-Y coating and two-step coating is 97, 7.3 and 4.1 mg/cm 2 respectively after hot corrosion at 900 °C for 100 h in Na2 SO4 +NaCl molten salts. The hot corrosion mechanism of the coating has been revealed.